2019
DOI: 10.3390/polym11081311
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Analysis of High-Strength Laminated Composites from Recycled Newspaper and HDPE

Abstract: Recycled newspaper (NP) shows excellent potential as a reinforcement for polymer composites. Herein, high-strength laminated composites were prepared by using NP laminas as reinforcement and high-density polyethylene (HDPE) films as matrix. Physical and mechanical properties of the laminated composites were measured. It was found that the flexural strength of the composites had a good linear relationship to its density, with R2 = 0.9853. The flexural and tensile strength of the composites at the maximum densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The results showed that the good mechanical strength of composites prepared using copy paper and newspaper respectively, and when the volume content of paper was 30%, the tensile and flexural strength of copy paper/PP laminated composites was the highest, about 85 MPa and 90 MPa [30,31]. As well as our previous research [32], high-strength laminates were prepared using newspaper layer as a reinforcing material and high density polyethylene (HDPE) film as the matrix. Such composite materials still need to be improved in terms of mechanical properties and processing efficiency.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results showed that the good mechanical strength of composites prepared using copy paper and newspaper respectively, and when the volume content of paper was 30%, the tensile and flexural strength of copy paper/PP laminated composites was the highest, about 85 MPa and 90 MPa [30,31]. As well as our previous research [32], high-strength laminates were prepared using newspaper layer as a reinforcing material and high density polyethylene (HDPE) film as the matrix. Such composite materials still need to be improved in terms of mechanical properties and processing efficiency.…”
Section: Introductionsupporting
confidence: 52%
“…It is shown that the use of the entire sheet of paper can help to improve some of the mechanical properties of the composite material. Compared to our previous work [32], the hot processing time had been cut in half and costs were lower. The composite material is of great significance for promoting the recycling of waste paper and improving the performance of polymer materials.…”
Section: Discussionmentioning
confidence: 70%
“…The 2 h water absorption rate and thickness swelling rate of composite samples at different SA concentrations were presented in Figure 8 . The modified composite samples showed better water resistance than other paper-based composite laminates that 49.3% (with 78.5% paper content) and 10.0% (with 30.0% paper content) water absorption rate were found in literature [ 10 , 12 ]. The 2-h water absorption rate of the composite samples was remarkably lower than that of pristine NP samples, since visible pores and voids in the NP sheets can be filled by HDPE, result in low water uptake [ 12 ].…”
Section: Resultsmentioning
confidence: 92%
“…The strength of paper sheets can be reduced significantly due to the dis-bonding of paper fibers after the absorption of water molecules, leading to a negative effect on mechanical performances of the composites [ 11 ]. The poor water resistance greatly limits the applications of this sort of composites, especially for composites with high paper content [ 12 ]. Although the composite can be protected laterally, it will inevitably produce scratches or even cracks when they applied outdoors.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure a sufficient compaction and infiltration of each layer, the time to press the thick composite was more than that to press the thin composite, which would cause the excessive permeation of HDPE into NP sheets at the laminar interface. It was found in the previous study that the excessive permeation of the HDPE would destroy the mechanical interlock between the NP fibers to break the continuity and integrity of the NP sheet, which would cause a negative impact on the enhancement of the NP sheets [22].…”
Section: Mechanical Propertiesmentioning
confidence: 99%